The Analysis Study of Risk Factor and Management of Perioperative Hypertension: A Comprehensive Systematic Review - Landong Sijabat; Guinanti Novettiandari (The Indonesian Journal of General Medicine, 2024)
Background: Perioperative hypertension, a common and significant clinical concern, occurs when blood pressure rises above normal levels during the perioperative period, encompassing the preoperative, intraoperative, and postoperative phases. This systematic review aims to analyze the existing literature on the risk factors, management strategies, and clinical outcomes associated with perioperative hypertension. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Perioperative hypertension management relies on anesthesia induction, monitoring, and antihypertensive medications. Proper control reduces complications like stroke, myocardial infarction, and organ damage, ensuring better outcomes. Consistent blood pressure management throughout the perioperative period is crucial for patient recovery.